Passive Optical LAN as an emerging LAN Architecture (International Journal of Engineering and Computer Science, 2015)
In a rapidly changing technological environment, though the Local Area Network helps an organization gain acompetitive edge, both domestically and internationally, but due to the fast changing technology, the environment oforganizations, and the growing role of information is challenging firms both large and small to replace their copper-basednetworks with fiber optics. Fiber-based Passive Optical LAN (POL) technology is a point-to-multipoint network architectureoptimized for local area network (LAN) environments to provide a fiber-to-the-desktop solution. (1) and has emerged as aparticularly promising alternative for enterprises in need of a secure, converged network with increased bandwidth. Passive opticalLAN (POL) technology platforms optimized for enterprise LAN environments have become available only in the last couple ofyears. Therefore in this paper authors have summarizes the potential use of POL for further use. We’ll then discuss traditionalLAN architecture, Passive Optical LAN components and further implications on network management, real estate, and energyconsumption.